Women, atrocity and punishment: a case study about the reasons of the women's movement to criminalize feminicide in Colombia (2019)
The women's movement in both Colombia and the world has a long tradition in the use of law. This work, in addition to dialogue with the literature on this subject, aims to analyze another aspect of the relationship of criminal law with women's movements that focuses its gaze, not on the deep criticism raised in criminal law, but in the growing punitive demand by these movements.